Odpowiedź:
a)
[tex] \sqrt[3]{4 \sqrt{4} } = \sqrt[3]{4 \times 2} = \sqrt[3]{8} = 2[/tex]
b)
[tex] \sqrt{3 \times \sqrt[3]{27} } = \sqrt{3 \times 3} = \sqrt{9} = 3[/tex]
c)
[tex] \sqrt[3]{36 \sqrt[3]{216} } = \sqrt[3]{36 \times 6} = \sqrt[3]{216} = 6[/tex]
d)
[tex] \sqrt[3]{ \sqrt[3]{512} } = \sqrt[3]{8} = 2[/tex]
e)
[tex] \sqrt{18 \sqrt[3]{8} } = \sqrt{18 \times 2} = \sqrt{36} = 6[/tex]
f)
[tex] \sqrt{5 \times \sqrt[3]{125} } = \sqrt{5 \times 5} = \sqrt{25} = 5[/tex]
g)
[tex] \sqrt[3]{9 \times \sqrt{9} } = \sqrt[3]{9 \times 3} = \sqrt[3]{27} = 3[/tex]
h)
[tex] \sqrt[3]{108 \times \sqrt{4} } = \sqrt[3]{108 \times 2} = \sqrt[3]{216} = 6[/tex]
i)
[tex] \sqrt{7 + \sqrt[3]{8} } = \sqrt{7 + 2} = \sqrt{9} = 3[/tex]
j)
[tex] \sqrt{20 - \sqrt[3]{64} } = \sqrt{20 - 4} = \sqrt{16} = 4[/tex]
k)
[tex] \sqrt[3]{19 + \sqrt{64} } = \sqrt[3]{19 + 8} = \sqrt[3]{27} = 3[/tex]
l)
[tex] \sqrt[3]{36 - \sqrt{81} } = \sqrt[3]{36 - 9} = \sqrt[3]{27} = 3[/tex]